If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p(p) + 8p = 0 Multiply p * p 4p2 + 8p = 0 Reorder the terms: 8p + 4p2 = 0 Solving 8p + 4p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '4p'. 4p(2 + p) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(2 + p)' equal to zero and attempt to solve: Simplifying 2 + p = 0 Solving 2 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + p = 0 + -2 p = 0 + -2 Combine like terms: 0 + -2 = -2 p = -2 Simplifying p = -2Solution
p = {0, -2}
| 10x-30=-80 | | (2b+1)(2b+1)=25 | | -5x+6y=69 | | 15x+17=-73 | | -6x-63=-75 | | -6-63=-75 | | x^3-6x-9=0 | | 3(x^2)+32x+45= | | x(x)-x-20=0 | | 30(x^2)+37x+10= | | 16=4(x-5)2 | | x(x)+12x-13=0 | | 8xy-120(x^2)(y^4)= | | x(x)-8x+12=0 | | (t+2)(t+2)=4 | | (t+2)2=4 | | 28-5x=4x+8 | | y=12x^2+203x+7 | | (6x+5)(4x+8)= | | 4x^2+6x+7=0 | | 3(n+1)=2(n+4) | | (-6x^2+10x+8)+(-8x^2+2x+6)= | | x^2+3x-x-3=0 | | 4x^2+7x-57= | | x^2-3x-x-3=0 | | -4(2.5x+8.7)=(1.4-9.2x)(6) | | 5x^2+9x-72= | | 9h=49 | | 7-5x-5-7x=5 | | 3-0.4k=3 | | s^3-3s^2-3=0 | | -3(x-2)=x |